1974
DOI: 10.1128/iai.9.5.897-902.1974
|View full text |Cite
|
Sign up to set email alerts
|

Differential Attachment by Piliated and Nonpiliated Neisseria gonorrhoeae to Human Sperm

Abstract: Piliated type 1 Neisseria gonorrhoeae attached to 50% of human sperm after incubation of mixtures in vitro for 15 min at 35 C. In contrast, nonpiliated type 4 N. gonorrhoeae attached to only 23% of sperm. Similar results were obtained with three different strains of N. gonorrhoeae. Treatment with heat or formaldehyde to kill bacteria did not affect the amount of attachment by piliated or nonpiliated types. Escherichia coli and N. subflava, other species of piliated bacteria, attached to about 40% of sperm, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…Studies with primary human urethral epithelial cells have shown that this mutant is significantly less invasive than its wild-type counterpart (unpublished data). Gonococci associating with human sperm cells were observed years ago, although the bacterial and/or host molecular mechanisms contributing to this interaction have not been characterized (James-Holmquest et al, 1974). The expression of two related polypeptides, H1 and H2, comprising human hepatic ASGP-R, with molecular weights of 46 and 52 kDa, respectively, has been reported by others .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies with primary human urethral epithelial cells have shown that this mutant is significantly less invasive than its wild-type counterpart (unpublished data). Gonococci associating with human sperm cells were observed years ago, although the bacterial and/or host molecular mechanisms contributing to this interaction have not been characterized (James-Holmquest et al, 1974). The expression of two related polypeptides, H1 and H2, comprising human hepatic ASGP-R, with molecular weights of 46 and 52 kDa, respectively, has been reported by others .…”
Section: Discussionmentioning
confidence: 98%
“…The hypothesis that gonococci might attach to human sperm and subsequently become transported through the male and female reproductive systems was investigated almost 30 years ago (Howard, 1971). A few years later, observation of specific attachment of piliated and non-piliated gonococci to human sperm cells suggested that factors other than pili are involved in the attachment process (James-Holmquest et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…(4) reported that only cells from the virulent colony types were piliated suggesting that pili may be linked to the property of virulence in the gonococcus . Furthermore, the piliated gonococci were found to have a greater ability to adhere to both tissue culture cells (9) and sperm cell surfaces (3), both of which could give these cells a selective advantage in the urinary tract . Other data suggest that pili may also aid this bacterium in resisting phagocytosis (7).…”
mentioning
confidence: 99%
“…IgM (A) and IgG (B) antibodies were detected by a dot-ELISA. numbers to the spermatozoal tails than to the heads (14)(15)(16)30).…”
Section: Discussionmentioning
confidence: 99%